Kuat Tekan Dan Sifat Fisik Beton OPC, OPC POFA, Dan PCC Menggunakan Air Gambut Sebagai Air Pencampur Beton - Redol Sianturi; Monita Olivia; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The use of peat water is often used as concrete mixing water in areas difficult to obtain clean water. Peat water containing a low pH is not recommended as concrete mixing water because it can reduce the quality of concrete. Mineral materials such as Palm Oil Fuel Ash (POFA) used in the concrete mix to increase the density and strength of the resulting. This study aims to assess the compressive strength and physical properties such as porosity and water sorptivity concrete using peat as concrete mixing water. Type of cement used in the concrete mixture is OPC, PCC, and OPC POFA 10%. Peat water for the research came from Rimbo Panjang, Kampar and POFA derived from PKS GAS, Kandis. Research results show that the peat water can still be used to mix concrete is still above the minimum strength of 90% of the normal compressive strength.Keywords: OPC, PCC, palm oil fuel ash(POFA), peat water